Experiences and wishes of women regarding systemic aspects of midwifery care in Germany: a qualitative study with focus groups - Elke Mattern; Susanne Lohmann; Gertrud M. Ayerle (BMC, 2017)
Abstract Background Knowledge of pregnant women's and mothers' viewpoints on midwifery care is crucial for its appropriate delivery and research. In Germany, comprehensive research to more fully understand women's needs in pregnancy, labour, birth and the postpartum period until weaning is lacking. International studies provide some knowledge of women's expectations, their choices, and subjective criteria indicating good midwifery care. Methods This study explores pregnant women's and mothers' experiences, needs and wishes regarding systemic aspects of midwifery care (access, availability, choices, model of midwifery care; maternity care in the healthcare system). 50 women participated in 10 focus groups in 5 states of Germany. The groups were heterogeneous with regard to age, parity, model of maternity care used, and rating of satisfaction. Women with limited educational years (n = 9) were personally contacted by midwives and reached by social media. Also, mothers living in a mother-child home (n = 6) or attending a peer group for grieving parents (n = 5) were included. The digitally documented focus groups were systematically analysed in an itinerary hermeneutic manner. Results Three themes were identified: (a) Knowledge or lack of awareness of midwifery care, (b) availability of and access to midwives, and (c) midwifery care in the healthcare system. Theme (a) entails the scope of midwifery care and the midwife's competence, but also a lack of information, inconsistent counselling, and difficulty identifying midwives. Theme (b) encompasses aspects such as the availability, accessibility and selection of a midwife, the effort involved in looking for a midwife, the challenge of transition points, and family midwives. Theme (c) relates interprofessional cooperation, gaps/inadequacies of care during latency phase, alternative models of care, and the importance of family and peer groups for women. Conclusions Midwifery care and research in Germany must address the issue of imparting relevant information about midwifery services. Interprofessional cooperation and management of transition points ought to be improved in the interests of the women concerned. Moreover, the quality of antenatal classes, support during latency phase, and intrapartum care in hospitals need to be addressed. Lastly, the special needs of vulnerable women in midwifery care must become a major focus in Germany.